PENGARUH MODEL RME BERBASIS ETNOMATEMATIS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD IT RIYADHUL HABIBI - Siti Asnik Kumala Sari; Ahmad Landong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this study is based on the low learning outcomes of students,lack of interest in learning, and the continued use of conventional methods inmathematics learning. This study aims to determine the effect of the RealisticMathematic Education (RME) model to improve the learning outcomes of fourthgrade students of SD IT Riyadhul Habibi in mathematics lessons on flat shapes.The research method used in this study is True Experimental Design using thePretest-Posttest Control Group Design approach. The subjects in this studyconsisted of two classes, namely the experimental class using the RME model andthe control class using direct learning. Each class consisted of 18 people. Theresults of data analysis showed that the average post-test score in theexperimental class was 80.06 while in the control class it was 70.5. There was anincrease of 19.5 or 31.9% in the experimental class from pretest to posttest. Whilein the control class it only increased by 8.8 or 14.3%. Hypothesis testing using thet-test showed a t-value of 2.424 with a p-value of 0.021 ¸ 0.05. So it can beconcluded that there is a significant difference between student learning outcomesin the experimental class using the RME model and the control class using directlearning.